High-Power Ho-Doped Sesquioxide Ceramic Laser In-Band Pumped by a Tm-Doped All-Fiber MOPA - Yongguang Zhao; Jun Wang; Weichao Yao; Zhenhua Shao; Chongfeng Shen; Danlei Yin; Ying Wang; Peng Liu; Wei Zhou; Dingyuan Tang; Deyuan Shen (IEEE Photonics Journal, 2018)
We report on a high-power Ho:Y2O3 ceramic laser in-band pumped by a homemade Tm-doped all-fiber MOPA at 1941 nm. The Ho:Y2O3 ceramics fabricated by vacuum sintering and hot isostatic pressing present uniform ceramic grain and high optical homogeneity. The 24.6 W output power at ∼2117 nm is successfully achieved by exploiting the advantages of in-band pumping technique, which to our knowledge is one order of magnitude higher than the previous results obtained from the Ho-doped sesquioxides ceramic lasers, indicating the power scalability of sesquioxides ceramic compared to other bulk materials in high-power laser.